CO2, NOx and SOx removal from flue gas via microalgae cultivation: A critical review. Issue 6 (30th April 2015) - Yen, Hong‐Wei; Ho, Shih‐Hsin; Chen, Chun‐Yen; Chang, Jo‐Shu
Abstract Flue gas refers to the gas emitting from the combustion processes, and it contains CO2, NOx, SOx and other potentially hazardous compounds. Due to the increasing concerns of CO2 emissions and environmental pollution, the cleaning process of flue gas has attracted much attention. Using microalgae to clean up flue gas via photosynthesis is considered a promising CO2 mitigation process for flue gas. However, the impurities in the flue gas may inhibit microalgal growth, leading to a lower microalgae‐based CO2 fixation rate. The inhibition effects of SOx that contribute to the low pH could be alleviated by maintaining a stable pH level, while NOx can be utilized as a nitrogen source to promote microalgae growth when it dissolves and is oxidized in the culture medium. The yielded microalgal biomass from fixing flue gas CO2 and utilizing NOx and SOx as nutrients would become suitable feedstock to produce biofuels and bio‐based chemicals. In addition to the removal of SOx, NOx and CO2, using microalgae to remove heavy metals from flue gas is also quite attractive. In conclusion, the use of microalgae for simultaneous removal of CO2, SOx and NOx from flue gas is an environmentally benign process and represents an ideal platform for CO2 reutilization.